Minimizing Risk Associated With Older Liver Donors by Matching to Preferred Recipients: A National Registry and Validation Study. Issue 9 (September 2018) - Haugen, Christine E.; Thomas, Alvin G.; Garonzik-Wang, Jacqueline; Massie, Allan B.; Segev, Dorry L.
Abstract : Background: Allografts from older liver donors (OLDs), 70 years or older are often discarded for fear of inferior outcomes. We previously identified "preferred recipients" who did not suffer the higher risk of graft loss and mortality associated with OLDs. Preferred recipients were first-time, non-status 1 registrants older than 45 years, body mass index less than 35, indication other than hepatitis C, and cold ischemia time less than 8 hours. Methods: We assessed the validity of the preferred recipient construct in a larger, more recent cohort (38 891 patients, 2006-2013). We compared recipients of OLD grafts to recipients of average liver donors (ALDs, age = 40-69) and ideal liver donors (ILDs, age = 18-39) grafts using multilevel Cox regression adjusting for recipient and transplant factors. Results: The use of OLD grafts in preferred recipients has increased from 2006 to 2013 ( P = 0.02). Preferred recipients Model for End-Stage Liver Disease scores ranged 6 to 40. Preferred recipients had similar 5-year all-cause graft loss (ACGL) with OLD versus ALD and ILD grafts (25.4% vs 24.5% and 21.6%). Conversely, nonpreferred recipients had higher 5-year ACGL with OLD versus ALD and ILD grafts (41.4% vs 32.9% and 25.6%). After adjustment, preferred recipients had similar graft loss with OLD versus ALD grafts (hazard ratio [HR], 0.92 1.081.27 ; P = 0.3) and ILD grafts (HR, 0.98 1.161.39, P = 0.09); however, nonpreferred recipients had higher ACGL risk with OLD grafts versus ALD (HR, 1.28 1.411.56, P < 0.001) and ILD grafts (HR, 1.50 1.671.86, P < 0.001). Similar trends are seen with mortality. Conclusions: Because preferred recipients comprise 43.3% (n = 2916) of the current waitlist and span the full range of Model for End-Stage Liver Disease scores, transplanted OLD allografts could be distributed without added risk of graft loss or mortality. Abstract : The authors have updated a previous study validating an approach to optimal use of livers from older donors.